PENGARUH INDIVIDUAL SPIRITUALITY DAN WORKPLACE SPIRITUALITY TERHADAP EMPLOYEE ENGAGEMENT PEGAWAI AGENSI PEMASARAN DIGITAL - Rahayu Sri Purnami; Syamsul Hadi Senen; Disman Disman; Eeng Ahman (Jurnal Manajemen Bisnis Performa, 2020)
ABSTRACTThis research discusses the influence of individual spirituality and workplace spirituality on employee engagement of digital marketing agency employees. Quantitative analysis is processed using structural equation modeling with the alternative method of partial least square. The results showed that individual spirituality had a positive and significant effect on employee engagement, the higher the individual spirituality, the increased employee engagement. Workplace spirituality has a positive and significant effect on employee engagement, the higher the workplace spirituality, the higher employee engagement will be. This research shows that to improve employee engagement of employees of digital marketing agencies, the majority of whom are millennials, can be done by paying more attention to their spirituality. Keyword: Individual Spirituality,Workplace Spirituality, Employee Engagement  ABSTRAKPenelitian ini membahas mengenai pengaruh individual spirituality dan workplace spirituality terhadap employee engagement para pegawai agensi pemasaran digital.  Analisis kuantitatif diolah menggunakan structural equation modeling dengan metode alternatif partial least square. Hasil penelitian menunjukkan bahwa individual spirituality berpengaruh positif dan signifikan terhadap employee engagement semakin tinggi individual spirituality maka employee engagement akan meningkat. Workplace spirituality berpengaruh positif dan signifikan terhadap employee engagement semakin tinggi workplace spirituality maka employee engagement akan meningkat. Penelitian ini menunjukkan bahwa untuk meningkatkan employee engagement para pegawai agensi pemasaran digital yang mayoritas adalah generasi milenial dapat dilakukan dengan lebih memperhatikan sisi spiritualitasnya.    Kata kunci: Individual Spirituality, Workplace Spirituality, Employee Engagement